Annual Plan 1998-99 Maharashtra State Part II - Planning Commission (Planning Commission, 1998)
Abstract Statement indicating sub-sector wise outlay and expenditure Abstract Statement showing the provision for Development Boards Abstract Statement indicating outlay on Centrally Sponsored Programmes Abstract Statement indicating outlay and expenditure in respect of Tribal Area Sub-Plan Abstract Statement indicating outlay and expenditure in respect of Special Component Plan Abstract Statement of District Plan outlay Statement indicating outlay and expenditure in respect of 20-Point Programmes.
Planning Department Government of Maharashtra